Entre a janela e o mundo: a poética da transformação da paisagem no Quadrilátero Ferrífero - José Márcio de Oliveira Lara (2023)
This thesis proposes a critical reading of the landscape transformation process in the geological province of Quadrilátero Ferrífero from the point of view of the artistic production in Minas Gerais. Within the cartographic outline in question, relief and mining are substantial presences in the conformation of geographic space and artistic imagery. The discussion addresses landscape issues of multiple natures, such as aesthetics, urbanistic, geographic, philosophical, and social, recommending the phenomenological perspective to think about the individual’s involvement with the Earth. The research recovers experiences, narratives and, above all, images around the identity rooting in the landscape and the reconfiguration regime imposed on it.